Role of SIRT-1 Gene in The Development of Diabetic Retinopathy - Fawzy, Dr. Laila H.; El-Din, Dr. Fatma Salah; Elshennawy, Dr. Salwa I.; Fouly, Dr. Marwa A.; Salem, Dr. Mai H. (South Eastern European Journal of Public Health, 2024)
Background: Diabetes mellitus (DM) has had a consistent increase in global prevalence. A common microvascular disease associated with diabetes is diabetic retinopathy (DR). As a complex, progressive, as well as asymptomatic neurovascular consequence of DM, DR is the leading cause of vision impairment and blindness in working-age people. The presence of retinal neovascularization classifies diabetic retinopathy (DR) as proliferative, non-proliferative, or diabetic macular edema. Aim of the Study: to evaluate the level of expression of mRNA sirt1- gene in cases of type 2 DM that have retinopathy or vulnerable to it. Patients and Methods: In this research, 60 cases (15 patients with diabetic retinopathy, 15 diabetic cases without retinopathy (PDR), and 30 non-diabetic controls) were recruited. SIRT1 mRNA expression from the two groups was analyzed. Notably, patients with DR exhibited a decrease in the expression of SIRT1 mRNA. ELISA was also used to measure the levels of IL-17 expression in the serum. The results showed that the sera of people with DR had higher levels of IL-17 expression than the sera of healthy people. Results: The findings of this research indicate that imbalanced IL-17 & SIRT1 expression levels may play a role in the etiology of DR, with SIRT1 potentially exerting a protective effect by suppressing IL-17 production.